The Effect of Tharthar-Tigris Canal on the Environmental Properties of the Tigris River Northern Baghdad, Iraq (Baghdad Science Journal, 2022)
The present study is considered the first on this sector of the Tigris River after 2003. It is designed for two aims, the first is to demonstrate the seasonal variations in physicochemical parameters of Tharthar-Tigris Canal and Tigris River; the second is to explain the possible effects of canal on some environmental properties in the Tigris River. Water samples were being collected monthly. Six sampling sites were selected, two on Tharthar Canal and four along the Tigris River, one before the confluence as a control site and the others downstream the confluence with the canal. For a period from January to December 2020, nineteen physicochemical parameters were investigated including air and water temperature, turbidity, electrical conductivity, salinity dissolved oxygen, percent oxygen saturation, biological oxygen demand, pH, total hardness, calcium, magnesium, sulphate, total dissolved solids, total suspended solids, total alkalinity, bicarbonate, nitrate and phosphate. The results showed that air and water temperatures were close in both Tigris and canal. The waters were well aerated, slightly alkaline and over saturation was recorded several times, while biological oxygen demand values did not exceed 5 mg/L along study period. The high values of conductivity, salinity, total dissolved solids, total hardness, calcium and sulphate ions in Tharthar water increased in the Tigris River below the confluence. Whereas, the low values of turbidity, TSS, total alkalinity and bicarbonate in the arm diluted in the main river. It has been concluded that Tharthar Canal affected the Tigris River by either increasing or diluting of the Tigris chemical components.